Reduction of microbiological contamination of poultry feed by electrophysical method - Borotov Atkham; Allanazarov Akmal; Baratov Dilshod; Murodov Xamidulla; Isayev Oybek; Tsyganko E.N. (BIO Web of Conferences)
The problem of microbial contamination of feed negatively affects the efficiency and safety of livestock production. In this study, the level of microbial contamination of various feeds for poultry was evaluated and the effectiveness of the electrophysical method of its reduction was studied. The objects of the study were compound feed for laying hens, plant-based feed mix and spring wheat grain. The selected samples were examined for the presence of total microbial count (TMC), total fungal count (TFC), as well as Salmonella and Escherichia coli. The experimental samples were microwave treated on a specialised processing line at 60 kW power, 915 MHz frequency and 90 seconds exposure. Analyses showed that the initial microbial contamination level varied with feed type, with no Salmonella or E. coli detected in the control samples. Microwave treatment resulted in a significant reduction in WMB and WBC counts in all feed types tested. The obtained results confirm the effectiveness of microwave EMF application to reduce microbial contamination of feeds.